Mast Cells Mediate Inflammatory Injury and Aggravate Neurological Impairment in Experimental Subarachnoid Hemorrhage Through Microglial PAR-2 Pathway - Qin, Bing; Peng, Yucong; Zhong, Chen; Cai, Yong; Zhou, Shengjun; Chen, Huaijun; Zhuang, Jianfeng; Zeng, Hanhai; Xu, Chaoran; Xu, Hangzhe; Li, Jianru; Ying, Guangyu; et al. (Frontiers in Cellular Neuroscience, 2021)
Subarachnoid hemorrhage (SAH) is a devastating cerebrovascular disease with high mortality and disability. Aberrant neuroinflammation has been identified as a critical factor accounting for the poor prognosis of SAH patients. Mast cells (MCs), the sentinel cells of the immune system, plays a critical in the early immune reactions and participate in multiple pathophysiological process. However, the exact role of MCs on the pathophysiological process after SAH has not been fully understood. The current study was conducted to determine the role of MCs and MC stabilization in the context of SAH. Mouse SAH model was established by endovascular perforation process. Mice received saline or cromolyn (MC stabilizer) or compound 48/80 (MCs degranulator). Post-SAH evaluation included neurobehavioral test, western blot, immunofluorescence and toluidine blue staining. We demonstrated that SAH induced MCs activation/degranulation. Administration of MC stabilizer cromolyn conferred a better neurologic outcome, decreased brain edema when compared with SAH+vehicle group. Furthermore, cromolyn significantly inhibited neuroinflammatory response and alleviated neuronal damage after SAH. However, pharmacologically activation of MCs with compound 48/80 dramatically aggravated SAH-induced brain injury and exacerbated neurologic outcomes. Notably, pharmacologically inhibition of microglial PAR-2 significantly reversed MCs-induced inflammatory response and neurological impairment. Additionally, the effect of MCs-derived tryptase in mediating neuroinflammation was also abolished by the microglial PAR-2 blockage in vitro. Taken together, MCs yielded inflammatory injury through activating microglia-related neuroinflammation after SAH. These data shed light on the notion that MCs might be a novel and promising therapeutic target for SAH.